Analisis Kandungan Parasetamol pada Jamu Fung Seh Cu Tong Wan Menggunakan Spektrofotometri Uv-Vis - Haryanto Haryanto; Nur Amaliah; Nisa Fatima; Nur Adila Ahmad; Fani Ramadani; Viona Safira Andi Saburo; Ahmad Fadhil; Sahruni Sahruni; Arini Azzahra; Andi Siti Ziskind Zakia (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Jamu is an Indonesian traditional medicine that has been used from generation to generation with the properties contained empirically proven. Herbs that will be marketed must meet safety and quality requirements and must not contain medicinal chemicals (BKO). However, the increasingly fierce competition in the herbal medicine industry has resulted in some herbal medicine makers adding medicinal chemicals (BKO) to the herbs they produce. Medicinal raw materials (BKO) commonly contained in herbal medicine, namely paracetamol. The research conducted analyzed the content of paracetamol in herbal medicine using the Uv-Vis spectrophotometric method with a wavelength of 240 nm to detect medicinal raw materials (BKO) and paracetamol levels contained in Fung seh cu tong wan herbal medicine. The analysis results from 3 replicates showed that the samples of jamu Fung seh cu tong wan were positive for paracetamol with levels of 0.0064%, 0.0104%, and 0.0184% and an average of 0.0117% was obtained.